Artistic practices and archaeological research - Gheorghiu, Dragoş; Gheorghiu, Dragoş; Barth, Theodor; Barth, Theodor (Archaeopress archaeology, 2019)
This volume - which has come about through a collaborative venture between Dragos Gheorghiu (archaeologist and professional visual artist) and Theodor Barth (anthropologist) - aims at expanding the field of archaeological research with an anthropological understanding of practices that include artistic methods